Effect of barleys having different liter weights on performance, economic value, ruminal fermentation of lambs, and nutrient digestibility - Güler, T; Şahin, Kazım; Çerçi, IH; Ertas, ON (Scientific Technical Research Council Turkey, 1999)
This experiment was conducted to determine the effects of diets containing barleys having different liter weights (It wt) on average daily gain, feed efficiency, profit margins, ruminal fermentation, and carcass characteristics of lambs and diet digestibility. 16 Akkaraman lambs approximately 8 mo old (averaging 30 kg) were used in a randomized design. Treatment groups consisting of barley grains and barley grains were classified to liter weights as follows: 1. Barley has 643 g It wt (Group 643). 2. Barley has 570 g It wt (Group 570). lambs were fed a diet of 80 % concentrate feed (98 % barley, 2 % supplement) and 20 % straw. Average daily gains and average daily dry matter intake for lambs fed diets containing barleys having 643 and 570 g It wt were 209.6, 169.6 g and 1361, 1357 g, respectively. Lambs fed diet containing barley having 643 g It wt had more efficient feed conversion than other group. Hot carcass quality of lambs fed diet containing barley having 643 g it wt was better than lambs fed diet containing 570 g It wt. Diet containing barley having 643 g it wt had higher digestibility of dry matter, organic matter, crude protein, crude fiber, ether extract and nitrogen free extract than diet containing barley having 570 g It wt. Barley having high it wt decreased the cost of I kg live weight gain. Molar percentage of ruminal acetate was lower but molar percentage of propianate and butyrate was higher in lambs fed diet containing barley having 643 g It wt compared to the other barley.
Keywords: barley; liter weight; performance; profit; ruminal fermentation; digestibility